Effectiveness of online differentiated instruction in term of students' mathematical problem solving ability - Siburian, Rosinta; Simanjuntak, Sinta Dameria; Simorangkir, Frida Marta (Jurnal Riset Pendidikan Matematika, 2022)
Differentiated instruction is proposed to ensure that students receive learning activities that meet their prior-ability, characters, or needs. This study aims to examine the mathematical problem-solving ability of students who received differentiation learning in comparison to those who attended conventional learning. Conducted in a Catholic Junior High School in Medan during the 2020/2021 academic year, this quasi-experimental study was set in Pretest-Posttest Control Group Design. The population in this study were all eigth-graders from 7 parallel groups with 31 people in each. The sample in this study was 22 students consisting of 11 students for the experimental class and 11 students for the control class. The results showed that the average value of students' mathematical problem-solving abilities who participated in differentiation learning was 71.02, while that of conventional learning was 62.73. The difference in the average value of students' mathematical problem-solving abilities in the experimental class and control class is 8.29. From the results of hypothesis testing, the value of tcount = 2.68 and ttable = 1.725 means that tcount > t table is 2.68 > 1.725. This means that Ha is accepted and Ho is rejected, hence, the mathematical problem solving ability of students who joined differentiation learning (Differentiated Instruction) is better than those who attended the conventional learning.